SEXUAL NATIONALISM: "I LOVE LITHUANIA" - VASILIAUSKAITĖ, NIDA (Politologija, 2013)
In 2011, the major Lithuanian commercial television channel LNK TV produced and broadcast a notorious reality show “I Love Lithuania”. Unlike similar local entertainment projects, this one was based on a particular political vision and had a strong political message behind. Moreover, it aimed at social engineering, providing some models of “being an exemplary Lithuanian”, “a good and normal citizen”, with the intent to change people’s mind inspiring them to feel national unity and pride and to “revolt” against the obscure Enemy. The article deals with the political message of the show, reconstructing it from different subtexts and surrounding circumstances, and puts it as a kind of aggressive militant ethnocentric nationalism potentially directed against the “West”, i. e. against Lithuania’s membership (“subjection to”) in the ES, going back to the pop-romanticism of the 19th century.The show, however, has one more, “unofficial”, but nonetheless developed topic – namely “love” in a plain sense of (heterosexual) “romance” and “making family”, articulated in sexist terms. According to my thesis, it is not a coincidence or just a “soft” subject added simply to amuse the public, but rather a necessary (but not sufficient) condition and logical supplement of the nationalist “love for one’s country”. The article analyses this kind of “love” as well, asking what are its functions in the show, what does it mean on the political level, and claiming that the nationalist “love” as the only way to relate oneself politically to the state in this “order of things” reveals the same sexist presuppositions: the two regimes are interdependent.